2012
DOI: 10.1089/neu.2011.2298
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breaching the Connective Sheaths of the Donor Nerve on Its Myelinated Sensory Axons and on Their Sprouting into the End-to-Side Coapted Nerve in the Rat

Abstract: The influence of breaching the connective sheaths of the donor sural nerve on axonal sprouting into the end-to-side coapted peroneal nerve was examined in the rat. In parallel, the effect of these procedures on the donor nerve was assessed. The sheaths of the donor nerve at the coaptation site were either left completely intact (group A) or they were breached by epineurial sutures (group B), an epineurial window (group C), or a perineurial window (group D). In group A, the compound action potential (CAP) of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…13 Oyamatsu et al 12 reported that deliberate donor nerve injury after creation of a perineurial window with ETS repair following a partial crush injury or partial neurotomy, promoted axon regeneration of the donor nerves, compared to simple perineurial opening, 7 days after surgery in a rat model. In our study, no marked functional impairments of the tibial nerve and gastrocnemius muscle were noticed in the group of ETS neurorrhaphy with an epineurial window at all time points after surgery as assessed by electrophysiology, myelinated axon recovery, muscle force, musclular fiber area, and wet muscle weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Oyamatsu et al 12 reported that deliberate donor nerve injury after creation of a perineurial window with ETS repair following a partial crush injury or partial neurotomy, promoted axon regeneration of the donor nerves, compared to simple perineurial opening, 7 days after surgery in a rat model. In our study, no marked functional impairments of the tibial nerve and gastrocnemius muscle were noticed in the group of ETS neurorrhaphy with an epineurial window at all time points after surgery as assessed by electrophysiology, myelinated axon recovery, muscle force, musclular fiber area, and wet muscle weight.…”
Section: Discussionmentioning
confidence: 99%
“…11 Kovacic et al found that an epineurial window or a perineurial window does not affect the average compound action potential area or the total number of myelinated axons in the donor sural nerves which were repaired in an ETS fashion as measured in peroneal nerves after 8 weeks postoperatively. 13 Oyamatsu et al 12 reported that deliberate donor nerve injury after creation of a perineurial window with ETS repair following a partial crush injury or partial neurotomy, promoted axon regeneration of the donor nerves, compared to simple perineurial opening, 7 days after surgery in a rat model. In our study, no marked functional impairments of the tibial nerve and gastrocnemius muscle were noticed in the group of ETS neurorrhaphy with an epineurial window at all time points after surgery as assessed by electrophysiology, myelinated axon recovery, muscle force, musclular fiber area, and wet muscle weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although regenerating axons are able to penetrate the epineurium and perineurium of the donor nerves, connective tissue sheath of the nerve does pose an obstacle to axon sprouting after ETS neurorrhaphy, 23 and research increasingly suggests that axonal damage in the donor nerve may provide a significant positive stimulus to axon sprouting. 11,21,[24][25][26] Therefore, it can reasonably be expected that ETS neurorrhaphy with deliberate injury in the donor hypoglossal nerve may result in larger numbers of regenerating fibers and better functional outcomes. It is worth mentioning that both the reconstruction techniques resulted in partial functional recovery at different levels, but no complete restoration of function was obtained.…”
Section: Discussionmentioning
confidence: 99%